Abnormal placental CD8+ T‐cell infiltration is a feature of fetal growth restriction and pre‐eclampsia. (16th September 2020) - Lager, Susanne; Sovio, Ulla; Eddershaw, Elizabeth; van der Linden, Margaretha W.; Yazar, Cansu; Cook, Emma; Happerfield, Lisa; Jessop, Flora A.; Sebire, Neil J.; Charnock‐Jones, D. Stephen; Smith, Gordon C. S.
Abstract : Key points: Placental pathological abnormalities are more frequently observed in complicated pregnancies than in healthy pregnancies. Infiltration of CD8 + T‐cells into the placental villous tissue occurred in both fetal growth restriction and pre‐eclampsia, whereas CD79α + B‐cell infiltration was only apparent with reduced fetal growth. Vascularization, fibrin depositions, macrophage and neutrophil infiltration in the placenta did not differ between healthy and complicated pregnancies. Abstract: Fetal growth restriction (FGR) and pre‐eclampsia are severe, adverse pregnancy outcomes. Alterations in placental histology are frequently reported in these pregnancy complications and are often based upon scoring by pathologists. However, many alterations are also observed in placenta from uncomplicated pregnancies. Moreover, knowledge of disease state may bias assessment. We sought to perform an objective comparison of placental microscopic appearance in normal and complicated pregnancies. Placental villous tissue ( n  = 823) and edge biopsies ( n  = 488) from 871 individual, singleton pregnancies were collected after delivery. Cases of small‐for‐gestational age (SGA) or pre‐eclampsia were matched with healthy controls. A subset of the SGA cases displayed signs of FGR. Cases of preterm delivery were also included. Tissue sections were stained with haematoxylin and eosin or antibodies for CD8, CD14, CD31, CD79α and elastase. Images were scored by two experienced pathologists for pathological features or analysed by image analysis and stereology. Analyses were performed blind to case–control status and gestational age. Volume fraction of T‐cells increased in placentas from pregnancies complicated by pre‐eclampsia (adjusted odds ratio (aOR) 1.46, 95% CI: 1.12–1.90) and FGR (aOR 1.64, 95% CI: 1.11–2.43), whereas B‐cells only increased in FGR (aOR 1.65, 95% CI: 1.05–2.60). Pathological abnormalities in villous tissue were reported in 21.4% (88/411) of complicated pregnancies and 14.3% (52/363) of controls (OR 1.62, 95% CI: 1.12–2.37). There were no differences in the fractions of endothelial cells, fibrin deposition, macrophages and neutrophils when comparing normal and complicated pregnancies. In conclusion, FGR and pre‐eclampsia are associated with T‐cell infiltration of the placenta and placental pathological abnormalities. Key points: Placental pathological abnormalities are more frequently observed in complicated pregnancies than in healthy pregnancies. Infiltration of CD8 + T‐cells into the placental villous tissue occurred in both fetal growth restriction and pre‐eclampsia, whereas CD79α + B‐cell infiltration was only apparent with reduced fetal growth. Vascularization, fibrin depositions, macrophage and neutrophil infiltration in the placenta did not differ between healthy and complicated pregnancies.